Impact of an adaptive CRT optimization algorithm on the risk of life-threatening ventricular arrythmias of heart failure patients. (25th November 2020) - Briongos Figuero, S; Estevez, A; Perez, M.L; Martinez-Ferrer, J.B; Alvarez, L; Anguera, I; Garcia, E; Perez-Lorente, F; Porres, M; Villacastin, J; Munoz-Aguilera, R
Abstract: Introduction: Adaptive cardiac resynchronization therapy (aCRT) algorithm provides ambulatory CRT optimization and synchronized left-ventricular pacing instead of conventional biventricular pacing. Purpose: To analyze the impact of aCRT on the risk of life-threatening ventricular arrythmia (VA) in patients with concomitant defibrillator therapy. Methods: Symptomatic HF patients, in sinus rhythm, with LVEF ≤35% and QRS complex ≥130 ms undergoing first CRT-defibrillator (CRT-D) implant were collected from the multicentre, prospective and nationwide UMBRELLA study (2012–2017). All device information was automatically stored and collected through the remote monitoring system. An experts committee analysed in a blinded manner all electrograms. The endpoint was first appropriate therapy (AT) delivered within ventricular fibrillation zone at 12-months follow-up. Results: 206 patients were collected (66.1±8.7 years; 73.3% male). Fifty nine patients composed the aCRT group and 147 composed the non-aCRT group. At implant, LBBB was present in 93% of patients, functional class III or IV in 69.9%, non-ischemic HF in 63.1% of patients and mean LVEF was 26.5±5.6%. Optimal medical treatment was achieved in a majority (B-blockers in 92%; RAASi in 89% and MRA in 72.2%). The percentage of ventricular pacing through 12 months was 96.1±9.4% in non-aCRT patients and 97.5±2.7% in aCRT patients (p=0.261). At 1-year of follow-up, 16 patients were delivered an AT (event rate: 7.8%). Most of these episodes (n=14) were due to sustained monomorphic ventricular tachycardia while the rest were caused by sustained polymorphic ventricular tachycardia/VF. A lower incidence of AT was observed in aCRT patients (3.4%) compared to non-aCRT patients (9.5%) but with no statistical differences (OR=0.33, CI 0.07–1.51, p=0.155). Conclusions: In patients undergoing CRT provided by aCRT algorithm the risk of malign VA after 1-year of follow-up was low. Randomized studies are needed to clarify the impact of this dynamic algorithm on the arrhythmic risk of HF patients. Funding Acknowledgement: Type of funding source: None